TRENDS AND STRUCTURAL CHANGES ON THE GAS MARKET UNDER CURRENT CONDITIONS - Andrei E. Shmagin (Статистика и экономика, 2016)
The popularity of natural gas as an energy source increasingly grows. The rate of demand growth and the gas market development depend on a variety of key conditions discussed in the paper. The current market situation and trends are analyzed in the context of the global balance of energy.